Metamorphic P–T evolution and tectonic implications of pelitic granulites in the Ji'an area, northeastern Jiao–Liao–Ji Belt, North China Craton. (15th April 2020) - Cai, Jia; Liu, Fulai; Liu, Pinghua; Wang, Fang
Graphical abstract: Highlights: The Ji'an pelitic granulites record peak and post-peak metamorphic stages. Phase equilibria modeling demonstrates clockwise P–T paths. The Ji'an granulites were involved in continental subduction or collision. Abstract: The Ji'an area in the Jiao–Liao–Ji Belt of the North China Craton contains garnet-cordierite-sillimanite pelitic granulites that preserve representative metamorphic reaction textures. Petrographic observations and quantitative phase equilibria modeling indicate clockwise P–T paths with near-isothermal decompression and decompressional cooling following the peak metamorphism. The peak metamorphic assemblage was garnet + biotite + K-feldspar + plagioclase + sillimanite + quartz + ilmenite + magnetite with P–T conditions of 9–11 kbar and 830–880 °C. The ensuing post-peak near-isothermal decompressional assemblage was garnet + biotite + cordierite + K-feldspar + plagioclase + quartz ± sillimanite ± magnetite ± ilmenite with P–T conditions of 4.5–7.5 kbar and 810–900 °C, and this assemblage was characterized by large amounts of matrix cordierite due to the biotite decompressional dehydration melting reaction of Bt + Sil + Qz ± Pl → Crd + Kfs ± Ilm + Melt. LA–ICP–MS U–Pb analyses of detrital and metamorphic zircons in the sillimanite–garnet–cordierite pelitic granulites yielded a protolith age of ~2000 Ma and a late Paleoproterozoic metamorphic age of 1890–1870 Ma. Moreover, LA–ICP–MS U–Pb dating of monazites revealed a similar metamorphic age of 1880–1840 Ma. It had been suggested in the earlier literature that the metapelitic rocks from the Ji'an area reached the amphibolite-facies with a counterclockwise P–T path. However, our results indicate a clockwise P–T path and a granulite-facies metamorphism. We find that granulite-facies metamorphism was widespread throughout the Jiao–Liao–Ji Belt, as at Ji'an, Southern Liaohe, Jiaobei, and Bengbu, and the clockwise P–T paths and similar metamorphic ages obtained for all those areas indicate that the granulite-facies metamorphism within the Jiao–Liao–Ji Belt was a response to Paleoproterozoic continent–continent subduction and the collision of the Longgang and Nangrim blocks of the North China Craton during the peak metamorphic stage, followed by post-collisional exhumation in the post-peak decompressional stage.